2017
DOI: 10.1002/dev.21546
|View full text |Cite
|
Sign up to set email alerts
|

School‐age children's neural sensitivity to horizontal orientation energy in faces

Abstract: Face processing mechanisms are tuned to specific low-level features including mid-range spatial frequencies and horizontal orientation energy. Behaviorally, adult observers are more effective at face recognition tasks when these information channels are available. Neural responses to face images also reflect these information biases: Face-sensitive ERP components respond preferentially to face images that contain horizontal orientation energy. How does neural tuning of face representations to horizontal inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…(previously T5-T6), and P9-10 on the 10-20 system (Luu & Ferree, 2005) and are largely consistent with prior studies examining N170 responses in children and adults (Balas & Stevenson, 2014;Balas, van Lamsweerde, Saville, & Schmidt, 2017). The time windows we selected to examine each component varied across age groups.…”
Section: Component-based Erp Analysissupporting
confidence: 70%
“…(previously T5-T6), and P9-10 on the 10-20 system (Luu & Ferree, 2005) and are largely consistent with prior studies examining N170 responses in children and adults (Balas & Stevenson, 2014;Balas, van Lamsweerde, Saville, & Schmidt, 2017). The time windows we selected to examine each component varied across age groups.…”
Section: Component-based Erp Analysissupporting
confidence: 70%
“…An investigation of how ERP components like the P100 and the N170/N290 respond to varying levels of mutual information in face and non-face fragments would be an important step towards linking the computational and behavioral evidence for fragments of intermediate complexity as a mid-level representation of face appearance to real neural outcomes. Recent results examining the sensitivity of these components to the low-level visual information in faces (horizontal vs. vertical orientation energy) has revealed that face-sensitive ERP components change their tuning to orientation sub-bands during middle childhood in a category-selective way (Balas et al, 2017), supporting behavioral work indicating similar outcomes for response latencies . Applying these same methods to intermediate complexity features in faces and non-faces would thus provide an important complementary look at the development of visual recognition during this age range.…”
Section: Discussionmentioning
confidence: 75%
“…Consistent evidence indicates that the processing of face identity is tuned to horizontally oriented input; it declines progressively as visual input is oriented away from horizontal, and reaches its minimum when based on vertically-oriented cues. This horizontal tuning is already present in infants and strengthens until adulthood [10][11][12]. We further showed that horizontally-filtered face images trigger the largest response in the Fusiform Face Area (FFA), a high-level visual region responding preferentially to faces ( [13]; see [14,15] for EEG evidence of a horizontal dependence of face-specialized neural responses at a latency corresponding to high-level processing stages).…”
Section: Introductionmentioning
confidence: 69%